2017
DOI: 10.22159/ijpps.2017v9i5.17834
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents, in Vitro Antioxidant Activity, Oral Acute Toxicity and Ld50 Determination of Moringa Oleifera Leaves

Abstract: Objective: The objective of this study was undertaken to estimate the total phenolic contents (TPCs), in vitro antioxidant of different solvent extracts of M. oleifera leaves, oral acute toxicity and LD50 determination of the 85% methanolic extract as well as the chromatographic isolation and identification of the extract constituents. Methods:The antioxidant activity of different solvent extracts of Moringa oleifera leaves were estimated using three antioxidant assays and the total phenolic contents (TPCs) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Similarly, in Lingaraju et al [35], synthesized ZnO nanoparticles showed good scavenging activity with inhibitory concentration (IC 50 ) value of 9.34 mg/ml. In a recent study, they have also got the similar results [36]. In a similar study, methanolic extract of Lantana camara showed minimum IC 50 value for DPPH assay (48.75±2.34 µg/ml) [37].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Similarly, in Lingaraju et al [35], synthesized ZnO nanoparticles showed good scavenging activity with inhibitory concentration (IC 50 ) value of 9.34 mg/ml. In a recent study, they have also got the similar results [36]. In a similar study, methanolic extract of Lantana camara showed minimum IC 50 value for DPPH assay (48.75±2.34 µg/ml) [37].…”
Section: Discussionmentioning
confidence: 53%
“…Absorbance was taken in UV-spectrometer in different time intervals with both the isolates in the particular wavelengths where they have shown higher activity in silver nanoparticles and ZnO nanoparticles production. Both the graphs showed an increase in absorbance in various time intervals (0, 6,12,18,24,30,36,42, and 48 hrs) (Figs. 7 and 8).…”
Section: Uv-spectrometer Analysis Of Silver and Zno Nanoparticlesmentioning
confidence: 95%
“…Antioxidant activity [25] of the extracts was performed using method 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging [26,27]. 1 ml of 0.1 mM solution of DPPH in methanol was added to 3 ml of the solution of all the extracts in ethanol at different concentrations (5,20,40,60,80, and 100 µg/ml).…”
Section: Antioxidant Assaymentioning
confidence: 99%
“…As the leaves of the plant possess antimicrobial potency, the stem bark was screened for antimicrobial activity [25,28]. Four microbes, i.e., Gram-positive bacteria such as Staphylococcus aureus and Bacillus subtilis while Gram-negative Escherichia coli and Klebsiella pneumoniae were used.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The AO potential and antiradical unit (AU) activity of EGB761 and GBME were estimated by both ABTS and DPPH assays [22].…”
Section: Radical Scavenging Assays (22'-azino-bis(3-ethylbenzothiazomentioning
confidence: 99%